Trend Penggunaan Bejana (Al-Aniyah) Dalam Konteks Klasik Dan Semasa Menurut Perspektif Hukum Islam - Norhidayah Pauzi; Sa’adan Man; Syed Mohd Jeffri Syed Jaafar; Mohd Hafiz Jamaludin; Madiha Baharuddin (USIM Press, 2024)
Vol. 26 No.1 (2021): October Issue